IMPROVING STUDENTS’ READING COMPREHENSION THROUGH THE USE OF POWER POINT IN READING SHORT STORIES - Bebena, Korneles; Pelenkahu, Noldy; Rorimpandey, Rinny S. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The purpose of this research was to determine whether power point as a learning media used for reading short stories can improve students' reading skills. This research was conducted at SMK Likupang. The sample used in this study was class X students of SMK Likupang consisting of 23 students. The research design used was an experimental design with a quantitative approach, this pre-experimental research was conducted using pre-test, and post-test treatments. The instrument in this study was a test in the form of a questions. 10 questions are multiple choice and 10 another are completion questions. After analyzing the data, it was found that the average value of the post-test of 85.22 with a standard deviation of 6,30 was higher than the average value of the pre-test which was only 57.82 with a standard deviation of 7,54. This means that the post-test results are superior to the pre-test results. So it can be concluded that power point can improve the reading skills of class X students at SMK Likupang